La contribution bolivienne à la COP 21 au prisme de la justice environnementale - Florence Bétrisey; Christophe Mager (EchoGéo)
The contribution presented in December 2015 at the Climate Conference (COP 21) in Paris by Bolivian officials enjoyed a certain media coverage. It proposed lines of action, allowing both to achieve a more "just" climate governance and to build a new "civilization horizon" breaking with the consumerist, extractive and capitalist model of development. This article aims to question, through the prism of the different dimensions of justice being mobilized (redistribution, recognition and participation), the notions of justice on which the Bolivian contribution is based. It identifies two levels: that of discourse, and that of the tools offered. We show that favouring a redistributive conception of justice, paradoxically the Bolivian contribution ultimately tends not to exceed the development model to which it objected.